PEMANFAATAN MINYAK JELANTAH UNTUK PEMISAHAN PATCHOULI ALKOHOL MINYAK NILAM DENGAN DESTILASI EKSTRAKTIF - Hidayatna, Deden; Ariyanto, Hermawan Dwi; Pudjihastuti, Isti (METANA, 2015)
Abstract                       Patchouli oil is an essential oil obtained from the leaves of patchouli (Pogostemon cablin) by distillation. Oil is a non-oil export commodities among the most volatile oil exports in Indonesia. Patchouli oil exports in 2004 amounted to 1295 tons, while exports of the whole essential oil was 2633 tons (BPS, 2006). So that nearly 50% of volatile oil exports, dominated by patchouli oil. Patchouli oil are not only used as perfuming ingredients, can also be used as a drag scent perfumes other perfuming ingredients that do not quickly lose aroma and more durable (fixative) in the manufacture of perfumes, cosmetics and soap. Even today, the patchouli oil many developed toward drug product. This is because the essential oil contains more than 24 types of sesquiterpene, which has the potential as anti-cancer compounds, anti-microbial, anti-inflamatory, antibiotics and anti-microbial and anti-tumor. One component of patchouli oil potential and have a very high sale value of patchouli alcohol. Almost all the components of patchouli alcohol can produce the flavor and health products and medicines, and some researchers have attempted to separate them. Therefore, it is necessary to separate the essential oil of patchouli alcohol by combining the extraction and distillation in one column using a solvent used frying oil. This process is known as extractive distillation. Used frying oil is a solvent that can bind impuritas and alter the relative volatility of components in the original condition. This research started with the design and manufacture vacuum extractive distillation. A preliminary study conducted to determine the pressure relatively well for use in the purification process pathcouli alcohol patchouli oil. This pressure was varied in two variables, 3, 4 and 5 mmHg with a temperature of 110, 120,130,140, and 150oC. While the distillation time set two, four, six and eight hours, expected in this range at all pathchouli alcohol distillate. sample of each distillate was analyzed using gas chromatografi. advantages of our lab is able to replace the function of n-hexane as a solvent that has been used conventionally and transformed to enable the use of waste cooking oil is recovered the former (oil Jelantah).Keyword :extractive destillation, flavour,patchouli oil